Educational financing contribution to the course and training institution (LKP) of Uswatun Hasanah, Aceh Besar District - Rina Fitriana; Murniati AR; Nasir Usman (AL-ISHLAH: Jurnal Pendidikan, 2022)
Education financing and contribution to education financing at the Course and Training Institute (LKP) at LKP Uswatun Hasanah is carried out through the implementation of management functions, namely planning, implementation, supervision and accountability. This study aims to determine the planning, use, supervision, and financial accountability at LKP Uswatun Hasanah in Aceh Besar District. The research approach is descriptive method. Data collection techniques were carried out through interviews, observations, and documentation studies as well as data analysis techniques used including data reduction activities, data presentation, and conclusion drawing/verification. Research subjects are LKP leaders, secretaries, instructors and treasurers of financial management management at LKP Uswatun Hasanah, Aceh Besar District. The results of the study show: (1) Program planning is carried out based on technical instructions for meeting 8 national education standards as a reference by involving the LKP Treasurer and secretary, and the lack of instructor involvement in the planned budgeting process, (2) The use of government assistance and student tuition funds is implemented. in accordance with the technical instructions and the planned program, (3) Supervision of the use of government assistance funds and student tuition funds is carried out by the head of the institution, the Education Office and the inspectorate. Supervision is carried out by comparing the planned program with its implementation, and (4) accountability for the use of funds has been carried out with the treasurer and secretary of the institution.